Obstructed labour in a Nigerian tertiary health facility: a mixed-method study - Ubom, Akaninyene Eseme; Ijarotimi, Omotade Adebimpe; Ogunduyile, Ifeoluwa Emmanuel; Omilakin, Ayobami; Nyeche, Solomon; Igbodike, Emeka Philip; Emmanuel, Ogunjide Olakunle; Orji, Ernest Okechukwu; Ikimalo, John Igemo; Adeyemi, Adebanjo Babalola (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Obstructed labour remains a leading cause of maternal and perinatal mortality and morbidity in sub-Saharan Africa. This study aimed to determine the incidence, causes, complications and outcomes of obstructed labour at the Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC), Ile-Ife, Osun state, Nigeria. Methods: A mixed methods approach was employed for this study. A 10-year retrospective review of all cases of obstructed labour managed at the OAUTHC, between January 1, 2008, and December 31, 2017, was done. Ten in-depth interviews were conducted for some selected patients. The quantitative data was analysed using SPSS version 24, while the qualitative data was analyzed with NVivo version 12. Results: The incidence of obstructed labour was 1.99%. Most of the patients were unbooked (217, 90.4%), primigravid (138, 57.5%), and either had no formal or only primary/secondary education (120, 50%). Cephalopelvic disproportion (CPD) was the commonest cause of obstructed labour (227, 94.6%). The most common maternal complication was wound infection (48, 20%). There were three maternal deaths, giving a case fatality rate of 1.25%. The most common foetal complication was birth asphyxia (85, 34.7%). The perinatal mortality rate was 18.8 %. From the qualitative arm of the study, reasons given by parturients who suffered obstructed labour, for avoiding hospitals for delivery, included religion, finance, fear of hospitals, faith/belief in mission homes/maternity houses, and proximity. Conclusions: Obstructed labour remains an important obstetric problem in our environment, contributing significantly to the burden of maternal and perinatal mortality and morbidity.